Implementasi Tes Terintegrasi Pendidikan Agama Islam dan Sains untuk Mengetahui Critical Thinking Peserta Didik Madrasah Tsanawiyah Ma’arif Udanawu Blitar - Nur Azizah (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
This study aims to describe the theoretical and empirical feasibility characteristics of the integrated test instrument of Islamic Religious Education and Science to determine critical thinking skills. This research uses Research and Development (R&D) research referring to the ADDIE model and follows the steps of developing modifications from the Oreondo and Dallo-Antonio models. The design of the critical thinking test instrument using Paul and Elder indicators was validated by two material expert lecturers by lecturers of the study of Integration of Islamic Education at Tribakti Islamic University of Kediri and Science and linguist lecturers of the Islamic Institute of Kediri. Data analysis uses quantitative descriptive analysis in the form of data from expert judgment from material experts and linguists. Implementation is carried out with individual and group trials of MTs learners. class VIII. The test instrument consists of 20 questions with the HOTS question category based on critical thinking to determine the critical thinking skills of students.